Environmental Toxicology Selected Entries from the Encyclopedia of Sustainability Science and Technology - Laws, Edward A. (Springer New York : Imprint: Springer, 2013)
Environmental Toxicology provides a detailed, comprehensive introduction to this key area of sustainability and public health research.  The broad coverage includes sections on ecological risk assessment, monitoring, mechanisms, fate and transport, prevention, and correctives, as well as treatment of the health effects of solar radiation and toxicology in the ocean.  The 23 state-of-the-art chapters provide a multi-disciplinary perspective on this vital area, which encompasses environmental science, biology, chemistry, and public health. Features authoritative, peer-reviewed entries from the Encyclopedia of Sustainability Science and Technology Covers a wide range of environmental toxicology research, from recreational water risk to biomarkers and metabolomics Written for an audience of undergraduate and graduate students, researchers, industry professionals, and policymakers.